Bicyclo[2.2.1]hept-2-en-7-yl 4-bromobenzoate - Barry A. Lloyd (Acta Crystallographica Section E, 2012)
The structure of the title compound, C14H13BrO2, which contains a norbornenyl group and a 4-bromobenzoate ester at the single C-atom bridge, has been redetermined [see McDonald & Trotter (1965). Acta Cryst. 19, 456–463] to modern standards to establish high-precision geometrical data to compare with norbornyl and other tetracyclic 4-bromobenzoates. Possible structural evidence is sought to help explain solvolytic reactivities.